(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
This article is part of the research theme: "Development of territories", examines the principles governing the actions of a local call over the Internet to the implementation of good governance in the highlands of West- Cameroon. The central approach is to demonstrate how the use of the Internet to the implementation of a local improves the perception and satisfaction of the population compared to the benefits of local managers. It also demonstrates that through local internet communication can be an important managerial tool promoting good governance in the CTD